Cultural codes : makings of a Black music philosophy : an interpretive history from spirituals to hip hop - Banfield, William C., 1961- (Lanham : Scarecrow Press, 2010)
"No art can survive without an understanding of, and dedication to, the values envisioned by its creators. No culture over time has existed without a belief system to sustain its survival. Black music is no different. In Cultural Codes: Makings of a Black Music Philosophy, William C. Banfield engages the reader in a conversation about the aesthetics and meanings that inform this critical component of our social consciousness." "By providing a focused examination of the historical development of Black music artistry, Banfield formulates a useable philosophy tied to how such music is made, shaped, and functions. In so doing, he explores Black music culture from three angles: history, education, and the creative work of the musicians who have moved the art forward. In addition to tracing Black music from its African roots to its various contemporary expressions, including jazz, soul, R&B, funk, and hip hop, Banfield profiles some of the most important musicians over the last century: W.C. Handy, Scott Joplin, Louis Armstrong, Duke Ellington, Count Basie, Mary Lou Williams, John Coltrane, James Brown, Jimi Hendrix, and Stevie Wonder, among others. Cultural Codes provides an educational and philosophical framework for students and scholars interested in the traditions, the development, the innovators, and the relevance of Black music."--BOOK JACKET.
Black notes and cultural codes : makings of a Black music philosophy -- A new Black music arts aesthetic -- A history of aesthetic definitions -- Hip to the hop -- A cultural education -- Black music studies -- African roots to blues, New Orleans, and ragtime -- Jazz : the new modern mode of being -- Race records, gospel, R & B, and urban blues -- Urban contemporary : soul, funk, and global -- Hip hop : connecting the dots -- Core values and the Black aesthetic code.
Includes bibliographical references and index.
Description based on online resource, title from digital title page (viewed on February 18, 2025)
English.
eBooks on EBSCOhost
Keywords: African Americans -- Music -- History and criticism; Popular music -- United States -- History and criticism; Musique populaire -- États-Unis -- Histoire et critique; MUSIC -- Ethnomusicology; African Americans -- Music; Popular music; United States; Musik; Schwärze; USA; Muziekfilosofie; Muziek; Zwarten; Criticism, interpretation, etc